Biomedical fully degradable polylactic acid polymer-based composite product and preparation method thereof
Through the pre-melting blending of polylactic acid polymers and polyp-dioxycyclohexanone and secondary pre-melting blending treatment, combined with the micro injection molding process, polylactic acid polymer-based composite micro products without the need for addition of compatibilizers/toughening agents are prepared, which solves the brittleness of polylactic acid polymers in medical devices and achieves the full degradability, good mechanical properties and biocompatibility of the material.
Patent Information
- Application Number
- CN202310490775.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-05-04
AI Technical Summary
When used in medical devices that require high toughness, existing polylactic acid polymers are prone to problems such as high brittleness and easy to break, and commonly used compatibility agents/toughening agents are not biodegradable, which affects their biocompatibility for degradation in the body.
Polylactic polymers and polyp-dioxycyclohexanone are used as raw materials, and polylactic polymer-based composite micro products are prepared without adding compatibilizers/toughening agents through pre-melting and secondary pre-melting blending treatment, combined with a micro injection molding process.
It realizes the full degradability, good mechanical properties and biocompatibility of polylactic acid polymer-based composite materials, and is suitable for biomedical devices, improving its toughness and stability in applications.
Smart Images

Figure CN116478517B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical polymer products and their molding and processing, and relates to a biomedical fully degradable polylactic acid polymer-based composite product and a preparation method thereof, and specifically to a fully degradable polylactic acid polymer-based composite micro-product prepared by a micro injection molding process. Background Art
[0002] Polylactic acid polymers are the most cost-effective biodegradable materials. They have good biocompatibility, are completely biodegradable, and have good mechanical properties. They meet the basic requirements of various medical device manufacturing and are widely used. However, their high hardness and poor toughness make them prone to high brittleness and easy fracture in application scenarios requiring toughness, such as bone screws, vascular clamps, medical microcatheters, and microneedle arrays. In addition, the selection of materials for such medical products and devices that are in direct contact with the human circulatory system has higher requirements: on the basis of ensuring good biocompatibility, they meet the properties of being completely biodegradable and have simple formula ingredients, which can make them more widely used. Among the many PLA toughening methods, blending with tough polymer materials that complement mechanical properties is an effective method. However, materials with good toughness, such as PBAT and polydioxanone (PPDO), have poor compatibility with PLA due to the good flexibility of their molecular chains, and compatibilizers must be added to improve the toughening effect of the PLA system. In existing research reports, Arruda et al. added the multifunctional epoxy chain extender Joncryl ADR 4368 as a compatibilizer to the PLA / PBAT system (Arruda LC, Magaton M, Bretas RES, et al. Influence of chain extender on mechanical, thermal and morphological properties of blown films of PLA / PBAT blends[J]. Polymer Testing, 2015, 43, 27-37); Xu et al. added silica-based Janus nanosheets as a compatibilizer to the PLA / PPDO system to enhance their toughening effect (Xu Z, Lin J, Chen J, et al. Synthesis, characterization and its compatibilization on polymer blends of arched Janus nanosheets[J]. Polymer Testing, 2021, 98).If PLA is directly blended with such tough materials to prepare composite materials without adding any compatibilizer, the prepared PLA / PBAT, PLA / PPDO and other blends will undergo phase separation when the PBAT or PPDO content reaches 5wt% due to poor compatibility (Yeh JT, Tsou CH, Huang CY, Chen KN, Wu CS, Chai WL, Compatible and crystallization properties of poly(lactic acid) / poly(butylene adipate-co-terephthalate) blends, Journal of Applied Polymer Science, 2010, 116, 680), and the interfacial bonding strength is low, resulting in a significant decrease in the mechanical properties of the corresponding composite materials, especially the impact toughness and elongation at break. This is inconsistent with the purpose of toughening and modifying PLA, making it difficult for medical and health devices such as bone screws and microneedle arrays to meet the toughness requirements, and they may break during use, limiting their application.
[0003] However, in the existing toughening modification technology, commonly used compatibilizers / toughening agents, such as multifunctional epoxides (Joncryl ADR4368), multi-walled carbon nanotubes (Hemmati M, Rahimi GH, Kaganj AB, et al. Rheological and Mechanical Characterization of Multi-Walled Carbon Nanotubes / Polypropylene Nanocomposites [J], Journal of Macromolecular Science Part B, 2008, 47 (6), 1176-1187) or silane compatibilizers. This type of compatibilizer / toughener is not biodegradable, and the degradation of PLA-based products containing added compatibilizers in the body will cause the compatibilizer to be directly exposed to the body environment. The metabolic process of epoxide or silane compatibilizers with good biocompatibility remains to be studied, and unpurified carbon nanotubes have biocompatibility and cytotoxicity problems (Sun Lan, Zhang Yingge, Biocompatibility of Carbon Nanotubes [J], Journal of Biomedical Engineering, 2008, (03), 742-746).
[0004] Therefore, if there is a polylactic acid polymer-based composite material that is biocompatible and fully degradable, and at the same time has excellent mechanical properties, it will be expected to be promoted and used as the next generation of biomedical device materials. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the above-mentioned background technology and provide a biomedical fully degradable polylactic acid polymer-based composite product and a preparation method thereof. The preparation method only uses polylactic acid polymers and polydioxanone, which originally have poor compatibility, as raw materials to prepare the composite product. Without adding compatibilizers / toughening agents and other additives / fillers, a polylactic acid polymer-based composite micro-product with fully degradable characteristics and good mechanical properties and biocompatibility can be prepared.
[0006] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0007] A method for preparing a biomedical fully degradable polylactic acid polymer-based composite product comprises the following steps:
[0008] (1) The following raw materials are mixed by weight to prepare a mixed material:
[0009] Polylactic acid polymer (PLP) 85-95 parts,
[0010] Polydioxanone (PPDO) 5-15 parts,
[0011] Wherein, the polylactic acid polymer and polydioxanone are 100 parts in total;
[0012] (2) subjecting the mixture obtained in step (1) to a pre-melt blending treatment, specifically, subjecting the mixture to melt blending, extrusion and granulation using a single-screw extruder to obtain a pre-treated polylactic acid polymer-based composite material;
[0013] (3) subjecting the pretreated polylactic acid polymer-based composite material obtained in step (2) to a secondary pre-melt blending treatment, specifically, subjecting the pretreated polylactic acid polymer-based composite material to melt blending, extrusion and granulation using a twin-screw extruder to obtain a polylactic acid polymer-based composite material that has undergone a secondary pre-treatment; wherein the screw speed of the twin-screw extruder is not less than 60 rpm;
[0014] (4) The polylactic acid polymer-based composite material obtained in step (3) and subjected to secondary pretreatment is subjected to micro injection molding to obtain a polylactic acid polymer-based composite product; wherein the process parameters of the micro injection molding are: injection speed 50-200 mm / s, mold temperature 30-60°C, injection pressure 1000-1500 bar, and melt temperature 180-200°C.
[0015] In this article, the polylactic acid polymer (PLP) and polydioxanone (PPDO) used in step (1) can be selected from conventional commercially available raw materials, such as conventional chemical raw material grade polylactic acid polymer and polydioxanone; in one of the technical solutions, in order to be better suitable for the preparation of biomedical devices, the raw materials used are preferably medical grade chemical raw materials.
[0016] It should be noted that in the technical solution of the present invention, the raw materials in step (1) are composed of polylactic acid polymer and polydioxanone, and there is no third raw material component of other fillers / auxiliaries, especially no added compatibilizer / extender / plasticizer / toughener.
[0017] Herein, the polylactic acid polymer (PLP) in step (1) is any one of the polylactic acid polymers (PLP) known in the art, such as polylactic acid (PLA, also known as polylactide), polylactic acid-co-glycolic acid (PLGA, also known as polylactide-co-glycolide), etc. In one preferred technical solution, the polylactic acid polymer (PLP) in step (1) is polylactic acid.
[0018] In addition, it should be noted that the mixture obtained in step (1) must be sufficiently dry before the pre-melt blending treatment. If necessary, it must be dried before the pre-melt blending treatment. The conventional drying treatment method for polymer materials in the prior art can be referred to, for example, the mixture is vacuum dried at 40 to 80°C for 6 to 12 hours.
[0019] In this article, the pre-melt blending treatment in step (2) is specifically to melt-blend and extrude the mixture into granules by using a single-screw extruder, wherein the melt-blending and extrusion granulation by using a single-screw extruder can refer to the contents recorded in the prior art for specific process parameters, especially the single-screw melt-blending and extrusion granulation process parameters of conventional polylactic acid polymer materials or mixed materials whose main raw material component is polylactic acid polymer; it can also be based on the general principle of melt-blending and extrusion granulation, with the temperature selected to be higher than the melting temperature of the polylactic acid polymer, and the melt-blending and extrusion granulation treatment is carried out at a conventional screw speed.
[0020] In one of the technical solutions, in step (2), the mixed material is melt-blended and extruded into granules using a single-screw extruder, and the specific process parameters are as follows: the melting temperature is 180-200° C., and the screw speed is 20-30 rpm.
[0021] In this article, the secondary pre-melt blending treatment in step (3) is specifically to melt blend and extrude the pretreated polylactic acid polymer-based composite material using a twin-screw extruder for granulation, wherein the process parameters of the melt blending and extrusion granulation using a twin-screw extruder, except for the screw speed, can refer to the contents recorded in the prior art, especially the twin-screw melt blending and extrusion granulation process parameters of conventional polylactic acid polymer materials or mixed materials whose main raw material component is polylactic acid polymer materials; it can also be based on the general principle of melt blending and extrusion granulation, the temperature is selected to be higher than the melting temperature of the polylactic acid polymer, and the melt blending and extrusion granulation treatment is carried out at a screw speed of not less than 60rpm.
[0022] In one of the technical solutions, in step (3), the pretreated polylactic acid polymer-based composite material is melt-blended and extruded into granules using a twin-screw extruder, and the specific process parameters are as follows: the melt temperature is 180-200°C, and the screw speed is 60-100rpm.
[0023] Based on the above preferred technical solution, when the polylactic acid polymer (PLP) is polylactic acid, it should be noted that the reason why the pre-melt blending treatment and the secondary pre-melt blending treatment are adopted is mainly because PLA and PPDO have poor compatibility, and it should be noted that the screw speed in the secondary melt blending treatment of twin-screw extrusion cannot be lower than 60rpm, which is significantly improved compared with the conventional process parameters, in order to further make the PLA / PPDO with poor compatibility achieve uniform submicron dispersion and prevent agglomeration. If any one melt blending treatment is missing, or the screw speed is too low in the twin-screw extrusion process, the dispersed phase size of the PLA / PPDO blend system increases and is unevenly distributed. In the subsequent micro-injection strong shear force field, it is difficult to have in-situ fiber formation, which has an adverse effect on the formation of the shishi-kebab structure and is difficult to achieve the toughening effect on PLA.
[0024] In addition, it should be noted that the pretreated polylactic acid polymer-based composite material obtained in step (2) and the secondary pretreated polylactic acid polymer-based composite material in step (3) must be sufficiently dried before the next process. If necessary, they must be dried before the next process. The conventional drying method for polymer materials in the prior art can be referred to, for example, vacuum drying the composite material at 40 to 80°C for 6 to 12 hours.
[0025] The inventive point of the present invention is that the inventors of the present invention found that when developing PLA-based composite materials for biomedical use, after sufficient pre-melt blending, the PLA / PPDO composite material, without the need to add a compatibilizer / toughening agent or other additives, has good mechanical properties when molded by a micro-injection molding process. This breaks the inherent thinking of those skilled in the art that a compatibilizer / toughening agent must be added when two polymer materials with poor compatibility are melt blended. The unique strong shear force field of the micro-injection molding process is utilized to allow the dispersed phase to be in-situ fiberized under the action of shear force. These sub-micron-level fibers uniformly dispersed in the matrix enable the product to achieve a toughening effect that is difficult to achieve with traditional processing methods.
[0026] The inventor verified through repeated experiments that the improvement of the above mechanical properties is stable, and explored its principle through electron microscopy, and found that in the process of micro injection molding, PPDO forms a micro-nano fiber structure after micro injection molding, and plays a key role in the subsequent generation of shish-kebab structure. Among them, the polylactic acid-based composite material that has been fully pre-melted and blended can be found through electron microscopy observation that PLA and PPDO are distributed in a "sea-island" structure, and there is a certain gap between the dispersed phase and the matrix, which proves that the compatibility of the two is poor. However, in the sample obtained after the polylactic acid-based composite material is molded by the micro injection molding process, the PPDO dispersed phase is stretched along the melt flow direction to form a submicron fibrous structure with a relatively large aspect ratio, and a clear shish-kebab highly oriented crystalline structure is formed along the melt flow direction. Among them, the shish structure is composed of submicron fibers of the PPDO dispersed phase, and the kebab structure is composed of PLA lamellae. Its formation mechanism is that there is an extremely strong shear stress field in micro injection molding, and the shear force induces crystallization.
[0027] This discovery fully verifies that PLA and PPDO, under the premise of poor compatibility, can form a highly oriented shish-kebab crystalline structure through a micro-injection molding process after sufficient pre-melt blending, thus having excellent mechanical properties without adding compatibilizers / toughening agents.
[0028] In this article, the polylactic acid polymer-based composite product finally prepared in step (4) is a conventional product that can be molded in the micro injection molding process, which mainly depends on the choice of its mold, including biomedical devices, such as bone screws, vascular clamps, medical microcatheters, nasal micro-fixation nails, microneedle arrays; it can also be non-biomedical devices, such as micro gears, micro-electromechanical parts, etc.
[0029] The present invention has the following beneficial effects:
[0030] (1) The technical solution of the present invention uses only polylactic acid polymers and polydioxanone, which originally have poor compatibility, as raw materials to prepare composite products. Without adding compatibilizers / toughening agents and other additives / fillers, a new process is explored to prepare biomedical and fully degradable polylactic acid polymer-based composite micro-products.
[0031] (2) The polylactic acid polymer-based composite product prepared by the technical solution of the present invention has the characteristics of being fully degradable, and has excellent mechanical properties and biocompatibility, and is expected to be promoted and used as the next generation of biomedical device materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the PPDO / PLA microneedle array prepared in Example 1 of the present invention. It can be seen that the prepared microneedle array has a complete structure, good replicability and a smooth surface.
[0033] Figure 2 The quenched cross-section SEM image (b) of the polylactic acid-based composite material obtained in step (3) of the embodiment of the present invention after secondary pretreatment and the quenched cross-section SEM image (a) of pure PLA. It can be clearly seen from the figure that the compatibility between PLA and PPDO is not good. Although they have been fully melt blended, there is still a certain gap between them.
[0034] Figure 3 The SEM image (b) of the quenched cross section of the PPDO / PLA strip prepared in Example 1 of the present invention along the melt flow direction and the SEM image (a) of the quenched cross section of the pure PLA strip.
[0035] Figure 4 The SEM image (b) of the cross section of the PPDO / PLA strip prepared in Example 1 of the present invention after etching and quenching along the melt flow direction and the SEM image (a) of the cross section of the pure PLA strip after etching. For the pure PLA figure (a), after etching the pure PLA micro injection molding stretching strip, only the transverse lamellar (kabab) crystal structure is formed. However, as shown in figure (b), for the PLA / PPDO blended micro injection molding sample, it is obvious that there is a clear shish-kebab highly oriented crystal structure formed along the melt flow direction.
[0036] Figure 5This is a line graph comparing the mechanical properties of the PPDO / PLA strips and pure PLA strips prepared in Example 9 of the present invention. It can be seen that the pure PLA sample exhibits brittle fracture, while the curve with a PPDO content of 10% exhibits a typical tough fracture of a crystalline polymer. The stress of pure PLA before the strain reaches 5% increases in direct proportion to the strain; the stress-strain curve of the 90 / 10PLA / PPDO micro-injection molded sample shows an obvious turning point at about 3%, and a thin neck appears due to yielding. In particular, the elongation at break in Figure (d) is significantly improved. The elongation at break of pure PLA is 3.9%, and the elongation at break of the sample with a PPDO content of 10% is significantly improved, reaching 45.4%, which characterizes the toughness.
[0037] Figure 6 This is a comparison line graph of the breaking load of the PPDO / PLA microneedles and pure PLA microneedles prepared in Example 1 of the present invention. It can be seen that when the PPDO addition amount is 10%, the maximum breaking load is 7.5N, and the maximum breaking displacement is 0.132mm, which is much higher than that of the pure PLA sample (breaking load is 3.23N, and breaking displacement is 0.66mm). DETAILED DESCRIPTION
[0038] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0039] A method for preparing a biomedical fully degradable polylactic acid polymer-based composite product comprises the following steps:
[0040] (1) The following raw materials are mixed by weight to prepare a mixed material:
[0041] Polylactic acid polymer (PLP) 85-95 parts,
[0042] Polydioxanone (PPDO) 5-15 parts,
[0043] Wherein, the polylactic acid polymer and polydioxanone are 100 parts in total;
[0044] (2) subjecting the mixture obtained in step (1) to a pre-melt blending treatment, specifically, subjecting the mixture to melt blending, extrusion and granulation using a single-screw extruder to obtain a pre-treated polylactic acid polymer-based composite material;
[0045] (3) subjecting the pretreated polylactic acid polymer-based composite material obtained in step (2) to a secondary pre-melt blending treatment, specifically, subjecting the pretreated polylactic acid polymer-based composite material to melt blending, extrusion and granulation using a twin-screw extruder to obtain a polylactic acid polymer-based composite material that has undergone a secondary pre-treatment; wherein the screw speed of the twin-screw extruder is not less than 60 rpm;
[0046] (4) The polylactic acid polymer-based composite material obtained in step (3) and subjected to secondary pretreatment is subjected to micro injection molding to obtain a polylactic acid polymer-based composite product; wherein the process parameters of the micro injection molding are: injection speed 50-200 mm / s, mold temperature 30-60°C, injection pressure 1000-1500 bar, and melt temperature 180-200°C.
[0047] In this article, the polylactic acid polymer (PLP) and polydioxanone (PPDO) used in step (1) can be selected from conventional commercially available raw materials, such as conventional chemical raw material grade polylactic acid polymer and polydioxanone; in one embodiment, in order to be better suitable for the preparation of biomedical devices, the raw materials used are preferably medical grade chemical raw materials.
[0048] It should be noted that in the technical solution of the present invention, the raw materials in step (1) are composed of polylactic acid polymer and polydioxanone, and there is no third raw material component of other fillers / auxiliaries, especially no added compatibilizer / extender / plasticizer / toughener.
[0049] In one embodiment, the polylactic acid polymer (PLP) in step (1) is any one of the polylactic acid polymers (PLP) known in the art, such as polylactic acid (PLA, also known as polylactide), polylactic acid-co-glycolic acid (PLGA, also known as polylactide-co-glycolide), etc. In one preferred embodiment, the polylactic acid polymer (PLP) in step (1) is polylactic acid.
[0050] In addition, it should be noted that the mixture obtained in step (1) must be sufficiently dry before the pre-melt blending treatment. If necessary, it must be dried before the pre-melt blending treatment. The conventional drying treatment method for polymer materials in the prior art can be referred to. In one embodiment, the mixture is vacuum dried at 40 to 80° C. for 6 to 12 hours.
[0051] In one embodiment, the polylactic acid polymer (PLP) in step (1) is 85 to 95 parts, for example, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts or any range or point value therebetween; the polydioxanone (PPDO) is 5 to 15 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or any range or point value therebetween.
[0052] In this article, the pre-melt blending treatment in step (2) is specifically to melt-blend and extrude the mixture into granules by using a single-screw extruder, wherein the melt-blending and extrusion granulation by using a single-screw extruder can refer to the contents recorded in the prior art for specific process parameters, especially the single-screw melt-blending and extrusion granulation process parameters of conventional polylactic acid polymer materials or mixed materials whose main raw material component is polylactic acid polymer; it can also be based on the general principle of melt-blending and extrusion granulation, with the temperature selected to be higher than the melting temperature of the polylactic acid polymer, and the melt-blending and extrusion granulation treatment is carried out at a conventional screw speed.
[0053] In one embodiment, the mixed material is melt-blended and extruded into granules by a single screw extruder in step (2), and the specific process parameters are as follows: the melting temperature is 180-200°C, and the screw speed is 20-30rpm. The melting temperature is 180-200°C, such as 180°C, 185°C, 190°C, 195°C, 200°C or any range or point value therebetween; the screw speed is 20-30rpm, such as 20rpm, 22rpm, 24rpm, 26rpm, 28rpm, 30rpm or any range or point value therebetween.
[0054] In this article, the secondary pre-melt blending treatment in step (3) is specifically to melt blend and extrude the pretreated polylactic acid polymer-based composite material using a twin-screw extruder for granulation, wherein the process parameters of the melt blending and extrusion granulation using a twin-screw extruder, except for the screw speed, can refer to the contents recorded in the prior art, especially the twin-screw melt blending and extrusion granulation process parameters of conventional polylactic acid polymer materials or mixed materials whose main raw material component is polylactic acid polymer materials; it can also be based on the general principle of melt blending and extrusion granulation, the temperature is selected to be higher than the melting temperature of the polylactic acid polymer, and the melt blending and extrusion granulation treatment is carried out at a screw speed of not less than 60rpm.
[0055] In one embodiment, the pretreated polylactic acid polymer-based composite material is melt-blended and extruded into granules using a twin-screw extruder in step (3), and the specific process parameters are as follows: the melt temperature is 180-200°C, and the screw speed is 60-100rpm. The melt temperature is 180-200°C, such as 180°C, 185°C, 190°C, 195°C, 200°C or any range or point value therebetween; the screw speed is 60-100rpm, such as 60rpm, 70rpm, 80rpm, 90rpm, 100rpm or any range or point value therebetween.
[0056] Based on the above preferred technical solution, when the polylactic acid polymer (PLP) is polylactic acid, it should be noted that the reason why the pre-melt blending treatment and the secondary pre-melt blending treatment are adopted is mainly because PLA and PPDO have poor compatibility, and it should be noted that the screw speed in the secondary melt blending treatment of twin-screw extrusion cannot be lower than 60rpm, which is significantly improved compared with the conventional process parameters, in order to further make the PLA / PPDO with poor compatibility achieve uniform submicron dispersion and prevent agglomeration. If any one melt blending treatment is missing, or the screw speed is too low in the twin-screw extrusion process, the dispersed phase size of the PLA / PPDO blend system increases and is unevenly distributed. In the subsequent micro-injection strong shear force field, it is difficult to have in-situ fiber formation, which has an adverse effect on the formation of the shishi-kebab structure and is difficult to achieve the toughening effect on PLA.
[0057] In addition, it should be noted that the pretreated polylactic acid polymer-based composite material obtained in step (2) and the secondary pretreated polylactic acid polymer-based composite material in step (3) must be sufficiently dried before the next process. If necessary, they must be dried before the next process. The conventional drying method for polymer materials in the prior art can be referred to. In one embodiment, the composite material is vacuum dried at 40 to 80°C for 6 to 12 hours.
[0058] In one embodiment, the process parameters of the micro injection molding in step (4) are: an injection speed of 50 to 200 mm / s, such as 50 mm / s, 60 mm / s, 70 mm / s, 80 mm / s, 90 mm / s, 100 mm / s, 110 mm / s, 120 mm / s, 130 mm / s, 140 mm / s, 150 mm / s, 160 mm / s, 170 mm / s, 180 mm / s, 190 mm / s, 200 mm / s or any range or point value therebetween; The tool temperature is 30-60°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any range or point value therebetween; the injection pressure is 1000-1500bar, for example, 1000bar, 1100bar, 1200bar, 1300bar, 1400bar, 1500bar or any range or point value therebetween; the melt temperature is 180-200°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C or any range or point value therebetween.
[0059] The inventive point of the present invention is that the inventors of the present invention found that when developing PLA-based composite materials for biomedical use, after sufficient pre-melt blending, the PLA / PPDO composite material, without the need to add a compatibilizer / toughening agent or other additives, has good mechanical properties when molded by a micro-injection molding process. This breaks the inherent thinking of those skilled in the art that a compatibilizer / toughening agent must be added when two polymer materials with poor compatibility are melt blended. The unique strong shear force field of the micro-injection molding process is utilized to allow the dispersed phase to be in-situ fiberized under the action of shear force. These sub-micron-level fibers uniformly dispersed in the matrix enable the product to achieve a toughening effect that is difficult to achieve with traditional processing methods.
[0060] The inventor verified through repeated experiments that the improvement of the above mechanical properties is stable, and explored its principle through electron microscopy, and found that in the process of micro injection molding, PPDO forms a micro-nano fiber structure after micro injection molding, and plays a key role in the subsequent generation of shish-kebab structure. Among them, the polylactic acid-based composite material that has been fully pre-melted and blended can be found through electron microscopy observation that PLA and PPDO are distributed in a "sea-island" structure, and there is a certain gap between the dispersed phase and the matrix, which proves that the compatibility of the two is poor. However, in the sample obtained after the polylactic acid-based composite material is molded by the micro injection molding process, the PPDO dispersed phase is stretched along the melt flow direction to form a submicron fibrous structure with a relatively large aspect ratio, and a clear shish-kebab highly oriented crystalline structure is formed along the melt flow direction. Among them, the shish structure is composed of submicron fibers of the PPDO dispersed phase, and the kebab structure is composed of PLA lamellae. Its formation mechanism is that there is an extremely strong shear stress field in micro injection molding, and the shear force induces crystallization.
[0061] This discovery fully verifies that PLA and PPDO, under the premise of poor compatibility, can form a highly oriented shish-kebab crystalline structure through a micro-injection molding process after sufficient pre-melt blending, thus having excellent mechanical properties without adding compatibilizers / toughening agents.
[0062] In this article, the polylactic acid polymer-based composite product finally prepared in step (4) is a conventional product that can be molded in the micro injection molding process, which mainly depends on the choice of its mold, including biomedical devices, such as bone screws, vascular clamps, medical microcatheters, nasal micro-fixation nails, microneedle arrays; it can also be non-biomedical devices, such as micro gears, micro-electromechanical parts, etc.
[0063] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0064] Example
[0065] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0066] 1. Raw materials
[0067] PLA: Nature Works 4032D, Mn = 10W, melting point about 170 ° C, glass transition temperature about 60 ° C, melt flow rate 7g / 10min (210 ° C, 2.16kg), provided by Suzhou Kaixinbao Engineering Plastics Co., Ltd.
[0068] PPDO: Mn = 25W, melting point of about 109 ° C, glass transition temperature of about -10 ° C, melt intrinsic viscosity of 2.0 dl / g (Ubbelohde viscometer), Shenzhen Boli Biomaterials Co., Ltd.
[0069] 2. Preparation method
[0070] (1) The following raw materials are mixed by weight to prepare a mixed material:
[0071] Polylactic acid (PLA) 85-95 parts,
[0072] Polydioxanone (PPDO) 5-15 parts,
[0073] Wherein, polylactic acid and polydioxanone are 100 parts in total;
[0074] (2) pre-melting and blending the mixture obtained in step (1), specifically, melt-blending and extruding the mixture into granules by a single-screw extruder to obtain a pre-treated polylactic acid-based composite material; wherein the specific process parameters of the single-screw extruder are as follows: melt temperature of 180° C., screw speed of 30 rpm;
[0075] (3) subjecting the pretreated polylactic acid-based composite material obtained in step (2) to a secondary pre-melt blending treatment, specifically, subjecting the pretreated polylactic acid-based composite material to melt blending, extrusion and granulation using a twin-screw extruder to obtain a polylactic acid-based composite material that has undergone a secondary pre-treatment; wherein the specific process parameters of the twin-screw extruder are as follows: a melt temperature of 180° C. and a screw speed of 80 rpm;
[0076] (4) preparing a polylactic acid-based composite product by micro-injection molding the polylactic acid-based composite material obtained in step (3) and subjected to secondary pretreatment; wherein the process parameters of the micro-injection molding are: injection speed 50-200 mm / s, mold temperature 30-60° C., injection pressure 1000-1500 bar, and melt temperature 180-200° C.;
[0077] The size parameters of the prepared microneedle array are: the base diameter is 12 mm, the thickness is 0.9 mm; the bottom diameter of the microneedle tip is 0.3 mm, the height is 0.6 mm, and it is distributed in a 6×6 array.
[0078] 3. Test methods
[0079] 3.1 Scanning electron microscopy (SEM)
[0080] The blend melt extrudate or micro-stretched sample was completely immersed in liquid nitrogen for 10 minutes and quenched along the melt flow direction. In order to more clearly observe the crystalline structure in the micro-injection molded strips, the strips quenched along the melt flow direction were etched in 0.05 mol / L NaOH methanol solution at 25°C for 24 hours to remove amorphous PLA. The etched strips were then ultrasonically cleaned in distilled water for 5 minutes to remove surface impurities. Finally, the samples were gold-sprayed and the JSM-5900LV SEM of JEOL, Japan, was used to observe the microscopic morphology of the samples at an accelerating voltage of 5kV.
[0081] 3.2 Tensile test
[0082] The micro tensile samples were tested using a 5567 universal material testing machine from Instron, USA. The experiment was carried out at a room temperature of 25°C and a tensile speed of 1 mm / min. Five groups of parallel samples were tested for each sample and the average value was taken.
[0083] 3.3 Compression test
[0084] The microneedle array compression experiment was carried out on an Electro Force 3220SERIESⅡ testing machine produced by Bose Corporation of the United States, where the compression displacement and compression frequency were 0.15 mm and 0.2 Hz, respectively.
[0085] Examples 1 to 3, Comparative Example 1
[0086] Examples 1 to 3 and Comparative Example 1 are based on different ratios of polylactic acid to polydioxanone as variables to prepare the mechanical properties of the obtained samples. At this time, the process parameters of micro injection molding are: injection speed 100 mm / s, mold temperature 40°C, injection pressure 1500 bar, melt temperature 190°C; the specific comparative performance is shown in Table 1 below
[0087] Table 1 Effect of PPDO content on the mechanical properties of PLA / PPDO blends
[0088]
[0089] Through the above experimental comparison, it is surprisingly found that when the PPDO content is 10wt%, the elongation at break and the compressive load of the sample are significantly improved, and the increase is nearly 2 times that of the comparative example 1. Under the condition of no addition of compatibilizer / toughening agent and other additives, the increase exceeds our expectations, which fully proves that it has the potential of excellent mechanical properties.
[0090] Embodiments 4 to 6
[0091] Examples 4 to 6 are based on the different melt temperatures in micro injection molding as variables to prepare the mechanical properties of the obtained samples. At this time, the PLA / PPDO ratio is fixed at 90 / 10, and other micro injection molding process parameters are: injection speed 100 mm / s, mold temperature 40°C, injection pressure 1500 bar; the specific comparative performance is shown in Table 2 below:
[0092] Table 2 Effect of melt temperature on mechanical properties of PLA / PPDO blends
[0093]
[0094] Through the above experimental comparison, it is found that when the melt temperature is selected at 180°C, the elongation at break of the sample can be further significantly improved.
[0095] Examples 7-8, Comparative Example 2
[0096] Examples 7 to 8 and Comparative Example 2 are based on different mold temperatures in micro injection molding as variables to prepare the mechanical properties of the obtained samples. At this time, the PLA / PPDO content is fixed at 90 / 10, and other micro injection molding process parameters are: injection speed 100 mm / s, injection pressure 1500 bar, melt temperature 180°C; the specific comparative performance is shown in Table 3 below:
[0097] Table 3 Effect of mold temperature on mechanical properties of PLA / PPDO blends
[0098]
[0099] Through the above experimental comparison, it is found that when the mold temperature is selected at 40°C, the elongation at break of the sample can be further significantly improved. It should be noted that when the mold temperature is selected at 80°C, the experiment found that the results of the elongation at break in the tensile test have poor repeatability. The reason is speculated to be that the 80°C mold temperature is close to the melting temperature of PPDO and higher than the crystallization temperature of PPDO. Therefore, the crystallization of the sample may not be completed after the injection molding is completed, and the degree of crystallization cannot be controlled, resulting in a large difference in the elongation at break of each spline. Therefore, although increasing the mold temperature is theoretically beneficial to the crystallization of PLA and improving the elongation at break of micro injection molding samples, the production cycle will be lengthened, the demolding process will be difficult to control, and continuous production will be affected. Therefore, it is not appropriate to use the method of increasing the mold temperature alone to improve the mechanical properties of the sample.
[0100] Examples 9 to 11, Comparative Example 3
[0101] Examples 9 to 11 are based on different injection speeds in micro injection molding as variables to prepare the mechanical properties of the obtained samples. At this time, the PLA / PPDO content is fixed at 90 / 10, and other micro injection molding process parameters are: mold temperature 40°C, injection pressure 1500 bar, melt temperature 180°C; the specific comparative performance is shown in Table 4 below:
[0102] Table 4 Effect of injection speed on mechanical properties of PLA / PPDO blends
[0103]
[0104] Comparative Example 3 in the above table is a sample strip prepared by using pure PLA.
[0105] Through the above experimental comparison, it is found that when the injection speed is selected at 200 mm / s, the elongation at break of the sample can be further significantly improved.
Claims
1. A method for preparing a biomedical fully degradable polylactic acid polymer-based composite product, characterized in that The following steps are involved: (1) Mix the following raw materials by weight to prepare a mixture: Polylactic acid 85~95 parts, 5-15 parts of polydioxanone, Wherein, the polylactic acid polymer and polydioxanone are 100 parts in total; (2) pre-melting and blending the mixture obtained in step (1), specifically, melt-blending and extruding the mixture into granules by using a single-screw extruder to obtain a pre-treated polylactic acid-based composite material; wherein the specific process parameters of the single-screw extruder are as follows: melt temperature of 180° C., screw speed of 30 rpm; (3) subjecting the pretreated polylactic acid-based composite material obtained in step (2) to a secondary pre-melt blending treatment, specifically, subjecting the pretreated polylactic acid-based composite material to melt blending, extrusion and granulation using a twin-screw extruder to obtain a polylactic acid-based composite material that has undergone a secondary pre-treatment; wherein the specific process parameters of the twin-screw extruder are as follows: a melt temperature of 180° C. and a screw speed of 80 rpm; (4) The polylactic acid-based composite material obtained in step (3) and subjected to secondary pretreatment is subjected to micro injection molding to obtain a polylactic acid-based composite product; wherein the process parameters of the micro injection molding are: injection speed 100 mm / s, mold temperature 40°C, injection pressure 1500 bar, and melt temperature 190°C.
2. The preparation method according to claim 1, characterized in that: The mixed material obtained in step (1), the pretreated polylactic acid-based composite material obtained in step (2), and the polylactic acid-based composite material obtained in step (3) after secondary pretreatment need to be dried before the next process.
3. The preparation method according to claim 2, characterized in that: The drying treatment is vacuum drying at 40-80° C. for 6-12 hours.
4. A polylactic acid-based composite product prepared by the method for preparing a biomedical fully degradable polylactic acid polymer-based composite product according to any one of claims 1 to 3.